THE SYMBOLIC AND MYTHOLOGICAL ELEMENTS IN W.B. YEATS'S DRAMATIC WORKS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2026)
William Butler Yeats is widely recognized as one of the most influential figures in modern Irish literature, whose dramatic works are deeply rooted in symbolism and mythology. This article examines the symbolic and mythological elements in Yeats’s plays, focusing on their artistic, philosophical, and cultural significance. Yeats employed symbols and myths not merely as decorative literary devices but as essential tools for expressing spiritual realities, national identity, and the complexities of human existence. Through the incorporation of Irish folklore, Celtic legends, and mystical symbolism, he created a distinctive dramatic world that transcends ordinary reality. The study analyzes how mythological characters, supernatural motifs, and symbolic imagery contribute to the thematic depth of Yeats’s drama and reflect his vision of history, destiny, and the human soul. The findings demonstrate that symbolism and mythology play a crucial role in shaping the structure, meaning, and aesthetic value of Yeats’s dramatic works.